Evaluation of Hyperimmunoglobulin M Syndrome by Flow Cytometry - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (TURKISH SOC IMMUNOLOGY, 2015)
Objectives: In this study, we discuss CD40 and CD40L expression findings in hyperimmunoglobuline M (HIGM) syndrome suspected patients obtained by flow cytometry. Patients and methods: Between May 2009 and February 2014, CD40 analysis was performed in 12 male (range, 4 months to 20 years) and eight female patients (range, 2 months to 28 years) and CD40 ligand (CD40L) analysis in eight male patients (range, 11 months to 20 years). Peripheral blood mononuclear cell (PBMC) samples were stained with anti-CD19, -CD45, -CD20 and -CD40 monoclonal antibodies and CD19(+)CD40(+) cells were detected in the flow cytometer. For the diagnosis of X-linked HIGM syndrome, isolated PBMCs were cultured in phorbol myristate acetate and ionomycin for four hours and then CD3(+)CD4(+)CD8(-)CD40L(+) cells were analyzed by flow cytometry. Results: Compared to the healthy controls, low CD40 expression in one female patient (0.09%) and low CD40L expression in three male patients (0.03%, 2.7% and 4%, respectively) were observed. Conclusion: Although flow cytometry is a quick and reliable method in the diagnosis of HIGM syndrome, additional genetic testing is required to establish the definite diagnosis.
Keywords: Autosomal recessive; CD40 ligand; CD40; flow cytometry; hyperimmunoglobulin M syndrome; X linked genetic disease; HYPER-IGM SYNDROME; IMMUNODEFICIENCY; DEFICIENCY